2015
DOI: 10.1002/cyto.b.21227
|View full text |Cite
|
Sign up to set email alerts
|

The utility of multiparametric seven‐color flow cytometry in the detection of double hit lymphoma in ascitic fluid samples

Abstract: Double-hit lymphoma (DHL) is a rare type of lymphoma with concurrent chromosomal translocations of C-MYC with BCL2 or BCL6, associated with unfavorable prognosis. We describe a case of DHL in a 79-year-old female patient previously diagnosed with diffuse large B-cell lymphoma (DLBCL) with an early relapse in the ascitic fluid. A seven-color multiparametric flow cytometry immunophenotyping study of the ascitic fluid was carried out, and revealed 99.78% of large in size and high cellular complexity B-cells posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…BCL2 was frequently positive by flow cytometry in D/THL, but was most strongly expressed within the BCL2 + /MYC + cases compared to the MYC + /BCL6 + and MYC + /BCL2 + /BCL6 + cases. This finding confirms the prior observations that MYC + /BCL6 + cases are less frequently BCL2 positive by immunohistochemistry ( 8,14 ), and that strong flow cytometric expression of BCL2 may be helpful in the correct clinicopathologic context to identify cases to assess for a BCL2 gene rearrangement ( 20 ). In addition, we confirm that aberrant underexpression of CD45, CD19, and/or CD20 is seen in a subset of D/THL, which generally falls within the spectrum previously reported in the literature ( Table 4 ) and does not significantly vary by genetic subtype.…”
Section: Discussionsupporting
confidence: 90%
“…BCL2 was frequently positive by flow cytometry in D/THL, but was most strongly expressed within the BCL2 + /MYC + cases compared to the MYC + /BCL6 + and MYC + /BCL2 + /BCL6 + cases. This finding confirms the prior observations that MYC + /BCL6 + cases are less frequently BCL2 positive by immunohistochemistry ( 8,14 ), and that strong flow cytometric expression of BCL2 may be helpful in the correct clinicopathologic context to identify cases to assess for a BCL2 gene rearrangement ( 20 ). In addition, we confirm that aberrant underexpression of CD45, CD19, and/or CD20 is seen in a subset of D/THL, which generally falls within the spectrum previously reported in the literature ( Table 4 ) and does not significantly vary by genetic subtype.…”
Section: Discussionsupporting
confidence: 90%
“…Accurate identification of DHL, so that appropriate management can be started, is therefore important (Friedberg, 2017). Major FC and pathology studies have reported that the immunophenotype of cells in DHL is characterized by high levels of CD10, CD38, BCL2, CD43, and Ki-67, as well as decreased amounts of CD19 and CD20 (Alsuwaidan et al, 2019;Cordoba et al, 2016;Platt, DeLelys, Preffer, et al, 2013;Wu et al, 2010). Our results show that the isolated evaluation of CD20 median fluorescence intensity, CD38% expression and median fluorescence intensity, CD45 intensity, Ki-67% expression, bcl-2% expression, CD10% expression, and CD43% expression cannot be used to differentiate DHL from BL or MYC-DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…The high sensitivity of this technique allows for its application even with limited samples, particularly in challenging scenarios where accessing lymph nodes is impractical. This was demonstrated in another case where FCM immunophenotyping of ascitic fluid detected a DHL in a relapsed DLBCL patient [179]. Moreover, evaluating early therapy response via FCM proved valuable in predicting outcome and optimizing the treatment strategy for a patient with primary BM B cell lymphoma [180].…”
Section: Case Studies Using Proteomicsmentioning
confidence: 94%